Open limestone mine road composite dust suppressant and preparation method thereof
By modifying the composite dust inhibitor of xanthan gum, flue-cured flue extract and zirconia, the problem of dust rising in open-pit limestone mines is solved, and a long-term dust suppression effect is achieved with high efficiency, safety and low cost.
Patent Information
- Application Number
- CN202411282402.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The open-pit limestone mine roads are prone to breaking due to temporary non-hardening properties, resulting in dust rising. The existing wet method and chemical dust reduction methods are not effective, and there are toxic side effects and high cost problems.
Modified xanthan gum, flue-cured flue extract and zirconia are used as composite dust inhibitors, and prepared by graft copolymerization and mechanical mixing to form a stable coating network to capture dust and provide long-term dust suppression effect.
It has achieved efficient dust suppression on open-pit limestone mine roads, has good wind corrosion, evaporation and degradation properties, significantly improved dust capture effect, and is safe and low in material costs.
Smart Images

Figure BDA0005042065470000061 
Figure BDA0005042065470000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust suppressants, in particular to a composite dust suppressant for open-air limestone mine roads and a preparation method thereof. Background Art
[0002] In the mining and transportation of open-pit mines, since temporary non-hardened mine roads are mainly a mixture of soil and rocks, the road surface is easily broken under the repeated rolling of heavy-loaded vehicles, and a large amount of dust will be raised when the natural wind or the passing of cars, which can easily lead to the problem of excessive dust concentration. High-concentration dust will not only affect the transportation capacity of vehicles and the efficiency of various mechanical equipment, but also cause low visibility on site, affecting the normal driving of vehicles, and causing serious safety hazards to operators.
[0003] At present, wet dust suppression or chemical dust suppression is mainly used to suppress dust on mine roads. However, although wet dust suppression is simple to operate, it has a short dust suppression cycle, high limitations, and poor results. Chemical dust suppression has problems such as low dust suppression rate, strong toxic side effects, and easy to cause secondary pollution. It also has defects such as complex processing technology and high cost. Summary of the invention
[0004] The purpose of the present invention is to provide a composite dust suppressant for open-pit limestone mine roads and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art and achieve efficient dust suppression for open-pit limestone mine roads.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a composite road dust suppressant, comprising the following raw material components in parts by weight:
[0007] 1.2-3.8 parts of modified xanthan gum, 0.6-0.8 parts of flue-cured tobacco extract and 0.4-0.5 parts of zirconium oxide.
[0008] In the present invention, the modified xanthan gum is prepared by graft copolymerization of acrylamide monomer and xanthan gum.
[0009] As a further preferred embodiment of the present invention, the preparation method of the modified xanthan gum comprises the following steps:
[0010] The acrylamide monomer, xanthan gum and a cross-linking agent are mixed in water, and then an initiator is added to obtain the modified xanthan gum through graft copolymerization.
[0011] As a further preferred embodiment of the present invention, the reaction temperature of the graft copolymerization is 50-90°C, and the reaction time is 4 hours. The preferred reaction temperature is 70°C.
[0012] As a further preferred embodiment of the present invention, the crosslinking agent is trimethylolpropane triglycidyl ether (TTE), and the initiator is potassium persulfate (K2S2O8).
[0013] As a further preferred embodiment of the present invention, the mass ratio of xanthan gum (XG), acrylamide monomer, crosslinking agent and initiator is: 1:(13-17):(0.3-0.9):(0.1-0.5).
[0014] As a further preferred embodiment of the present invention, the mass ratio of xanthan gum to water is 1:150-300.
[0015] In the present invention, acrylamide monomer and xanthan gum gradually form cross-linking and network structures during the copolymerization process, and the obtained modified xanthan gum component can ensure rapid capture of dust after spraying, and exert wetting, cohesion and bonding effects.
[0016] As a further preferred embodiment of the present invention, the method for preparing the flue-cured tobacco extract comprises the following steps:
[0017] The flue-cured tobacco is boiled with water, and the filtrate is concentrated and adjusted to have an alcohol content of 28-38%. The precipitate is discarded after centrifugation, and the alcohol content of the filtrate is adjusted again to have an alcohol content of 55-60%. The precipitate is collected after standing and dried to obtain the flue-cured tobacco extract.
[0018] Furthermore, during the preparation of the flue-cured tobacco extract, anhydrous ethanol is used to adjust the alcohol content of the system.
[0019] In the present invention, zirconium oxide can react with the calcium oxide component in the limestone dust to obtain a complex, and then work together with the modified xanthan gum and the flue-cured tobacco extract component to form a stable coating network. The coating is not easy to break and can withstand the crushing caused by heavy-loaded vehicles, thereby achieving an excellent dust coating effect and effectively suppressing secondary dust.
[0020] The composite dust suppressant of the present invention exhibits long-term and stable dust suppression performance, and shows good wind erosion resistance, evaporation resistance, weather resistance and degradation resistance, and can bring significant economic and social environmental benefits to the field of limestone dust control.
[0021] The second technical solution of the present invention is to provide a road composite dust suppressant emulsion containing the above-mentioned raw material components.
[0022] As a further preferred embodiment of the present invention, the road composite dust suppressant emulsion comprises the following raw material components in parts by mass:
[0023] 1.2-3.8 parts of modified xanthan gum, 0.6-0.8 parts of flue-cured tobacco extract, 0.4-0.5 parts of zirconium oxide, 0.4-0.8 parts of surfactant, 5-8 parts of glycerol and 80-90 parts of water.
[0024] As a further preferred embodiment of the present invention, the surfactant is one or more of Taiko oil, cocamidopropyl betaine or sodium dodecylbenzene sulfonate.
[0025] The composite dust suppressant in the form of an emulsion can increase the wetting ability of the dust suppressant on dust, has excellent water retention performance, and has a better dust suppression effect.
[0026] The third technical solution of the present invention is to provide a method for preparing the above-mentioned road composite dust suppressant emulsion, comprising the following steps:
[0027] The modified xanthan gum, flue-cured tobacco extract and zirconium oxide are mechanically mixed and water is added, and the mixture is stirred for reaction. Then, a surfactant and glycerin are added to the reaction system and stirred evenly to obtain the composite road dust suppressant.
[0028] A fourth technical solution of the present invention is to provide the application of the above-mentioned composite road dust suppressant or composite road dust suppressant emulsion in dust suppression on open-pit limestone mine roads.
[0029] The composite dust suppressant of the invention has a wide range of formula component materials, a scientific and reasonable ratio, is degradable, low cost, non-toxic, harmless, and has the advantages of long-term dust suppression. It has an obvious effect on suppressing limestone dust and can greatly improve the dust capture effect of the dust suppressant solution on limestone dust. The preparation method is simple and is suitable for large-scale industrial production.
[0030] The present invention discloses the following technical effects:
[0031] The composite dust suppressant of the invention has excellent dust suppression effect, has no adverse effect on soil, and has certain water retention, and can meet the dust problem caused by soil and rock crushing caused by heavy-loaded vehicles rolling on mine roads.
[0032] The raw materials of the composite road dust suppressant of the present invention are widely available, and the manufacturing process is simple. It can effectively capture fine dust in the air, aggregate, adsorb and settle, and form a continuous and complete film on the surface of the dust, with good effect. The dust suppressant prepared by the present invention is biodegradable and suitable for market promotion and application. DETAILED DESCRIPTION
[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0034] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0038] Unless otherwise specified, "parts" in the present invention are parts by mass.
[0039] Example 1 Preparation of composite road dust suppressant
[0040] Preparation of modified xanthan gum:
[0041] (1) dissolving xanthan gum (XG) in distilled water at a volume of 150 times its mass at room temperature to obtain a xanthan gum solution;
[0042] (2) Add acrylamide (AM) and trimethylolpropane triglycidyl ether (TTE) to the xanthan gum solution of step (1) in sequence, stir for 30 minutes, and then pass N2 to remove dissolved oxygen; then heat the reaction system to 50°C, add potassium persulfate, and react for 4 hours to obtain a uniform and stable hydrogel-type modified xanthan gum.
[0043] Among them, the mass ratio of xanthan gum, acrylamide, TTE and potassium persulfate is 1:17:0.9:0.3.
[0044] Preparation of flue-cured tobacco extract:
[0045] The flue-cured tobacco was boiled in water for 3 times, each time for 1 hour. The decoction was collected and concentrated, and then anhydrous ethanol was added to adjust the alcohol content to 28%. After centrifugation, the precipitate was discarded, and anhydrous ethanol was added again to adjust the alcohol content of the filtrate to 55%. After standing for 5 hours, the precipitate was collected and dried to obtain the flue-cured tobacco extract.
[0046] Preparation of composite road dust suppressant:
[0047] 1.2 parts of modified xanthan gum, 0.68 parts of flue-cured tobacco extract and 0.4 parts of zirconium oxide were mechanically mixed and 80 parts of water were added, and stirred for reaction. Then, 0.4 parts of a surfactant and 5 parts of glycerol were added to the reaction system to obtain a composite road dust suppressant.
[0048] Example 2
[0049] Preparation of modified xanthan gum:
[0050] (1) dissolving xanthan gum (XG) in distilled water (200 times its mass) at room temperature to obtain a xanthan gum solution;
[0051] (2) Add acrylamide (AM) and trimethylolpropane triglycidyl ether (TTE) to the xanthan gum solution of step (1) in sequence, stir for 30 minutes, and then pass N2 to remove dissolved oxygen; then heat the reaction system to 60°C, add potassium persulfate, and react for 4 hours to obtain a uniform and stable hydrogel-type modified xanthan gum.
[0052] Among them, the mass ratio of xanthan gum, acrylamide, TTE and potassium persulfate is 1:15:0.5:0.1.
[0053] Preparation of flue-cured tobacco extract:
[0054] The flue-cured tobacco was boiled in water for 3 times, each time for 1 hour. The decoction was collected and concentrated, and then anhydrous ethanol was added to adjust the alcohol content to 35%. After centrifugation, the precipitate was discarded, and anhydrous ethanol was added again to adjust the alcohol content of the filtrate to 60%. After standing for 6 hours, the precipitate was collected and dried to obtain the flue-cured tobacco extract.
[0055] Preparation of composite road dust suppressant:
[0056] 3.8 parts of modified xanthan gum, 0.8 parts of flue-cured tobacco extract and 0.5 parts of zirconium oxide were mechanically mixed and 90 parts of water were added, and stirred for reaction. Then, 0.7 parts of a surfactant and 7 parts of glycerol were added to the reaction system to obtain a composite road dust suppressant.
[0057] Example 3
[0058] Preparation of modified xanthan gum:
[0059] (1) dissolving xanthan gum (XG) in distilled water at a volume of 150 times its mass at room temperature to obtain a xanthan gum solution;
[0060] (2) Add acrylamide (AM) and trimethylolpropane triglycidyl ether (TTE) to the xanthan gum solution of step (1) in sequence, stir for 30 minutes, and then pass N2 to remove dissolved oxygen; then heat the reaction system to 65°C, add potassium persulfate, and react for 4 hours to obtain a uniform and stable hydrogel-type modified xanthan gum.
[0061] Among them, the mass ratio of xanthan gum, acrylamide, TTE and potassium persulfate is 1:14:0.6:0.3.
[0062] Preparation of flue-cured tobacco extract:
[0063] The flue-cured tobacco was boiled in water for 3 times, each time for 1 hour. The decoction was collected and concentrated, and then anhydrous ethanol was added to adjust the alcohol content to 33%. After centrifugation, the precipitate was discarded, and anhydrous ethanol was added again to adjust the alcohol content of the filtrate to 58%. After standing for 5 hours, the precipitate was collected and dried to obtain the flue-cured tobacco extract.
[0064] Preparation of composite road dust suppressant:
[0065] 2.5 parts of modified xanthan gum, 0.7 parts of flue-cured tobacco extract and 0.4 parts of zirconium oxide were mechanically mixed and 80 parts of water were added, and stirred for reaction. Then, 0.8 parts of a surfactant and 8 parts of glycerol were added to the reaction system to obtain a composite road dust suppressant.
[0066] Example 4
[0067] Preparation of modified xanthan gum:
[0068] (1) dissolving xanthan gum (XG) in distilled water at a volume of 150 times its mass at room temperature to obtain a xanthan gum solution;
[0069] (2) Add acrylamide (AM) and trimethylolpropane triglycidyl ether (TTE) to the xanthan gum solution of step (1) in sequence, stir for 30 minutes, and then pass N2 to remove dissolved oxygen; then heat the reaction system to 55°C, add potassium persulfate, and react for 4 hours to obtain a uniform and stable hydrogel-type modified xanthan gum.
[0070] Among them, the mass ratio of xanthan gum, acrylamide, TTE and potassium persulfate is 1:16:0.3:0.5.
[0071] Preparation of flue-cured tobacco extract:
[0072] The flue-cured tobacco was boiled in water for 3 times, each time for 1 hour. The decoction was collected and concentrated, and then anhydrous ethanol was added to adjust the alcohol content to 36%. After centrifugation, the precipitate was discarded, and anhydrous ethanol was added again to adjust the alcohol content of the filtrate to 60%. After standing for 5 hours, the precipitate was collected and dried to obtain the flue-cured tobacco extract.
[0073] Preparation of composite road dust suppressant:
[0074] 2.7 parts of modified xanthan gum, 0.7 parts of flue-cured tobacco extract and 0.5 parts of zirconium oxide were mechanically mixed and 85 parts of water were added, and stirred for reaction. Then, 0.7 parts of a surfactant and 6 parts of glycerol were added to the reaction system to obtain a composite road dust suppressant.
[0075] Example 5
[0076] Preparation of modified xanthan gum:
[0077] (1) dissolving xanthan gum (XG) in distilled water at a volume of 150 times its mass at room temperature to obtain a xanthan gum solution;
[0078] (2) Add acrylamide (AM) and trimethylolpropane triglycidyl ether (TTE) to the xanthan gum solution of step (1) in sequence, stir for 30 minutes, and then pass N2 to remove dissolved oxygen; then heat the reaction system to 70°C, add potassium persulfate, and react for 4 hours to obtain a uniform and stable hydrogel-type modified xanthan gum.
[0079] Among them, the mass ratio of xanthan gum, acrylamide, TTE and potassium persulfate is 1:13:0.45:0.3.
[0080] Preparation of flue-cured tobacco extract:
[0081] The flue-cured tobacco was boiled in water for 3 times, each time for 1 hour. The decoction was collected and concentrated, and then anhydrous ethanol was added to adjust the alcohol content to 38%. After centrifugation, the precipitate was discarded, and anhydrous ethanol was added again to adjust the alcohol content of the filtrate to 57%. After standing for 5 hours, the precipitate was collected and dried to obtain the flue-cured tobacco extract.
[0082] Preparation of composite road dust suppressant:
[0083] 2.2 parts of modified xanthan gum, 0.7 parts of flue-cured tobacco extract and 0.5 parts of zirconium oxide were mechanically mixed and 90 parts of water were added, and stirred for reaction. Then, 0.6 parts of a surfactant and 5 parts of glycerol were added to the reaction system to obtain a composite road dust suppressant.
[0084] Comparative Example 1
[0085] The only difference from Example 1 is that zirconium oxide is replaced by an equal amount of sodium alginate.
[0086] Comparative Example 2
[0087] The only difference from Example 1 is that the preparation step of xanthan gum modification is not performed, and the modified xanthan gum component in the composite road dust suppressant is replaced by an equal amount of xanthan gum.
[0088] Comparative Example 3
[0089] The only difference from Example 1 is that the flue-cured tobacco is replaced by beet leaves, the beet leaves are used as raw materials for extraction, and the obtained beet leaf extract is used to replace the flue-cured tobacco extract in an equal amount.
[0090] The performance of the composite road dust suppressant was tested: the composite road dust suppressant prepared in the embodiment and the comparative example was mixed and dissolved with water (15°C tap water) at a mass ratio of 1:10, and after stirring evenly, the obtained solution was heated to 2 L / m 2 The spraying amount was sprayed on the surface of the open-pit limestone mine road to test the water retention rate and dust suppression rate.
[0091] The calculation formula of water retention rate is as follows:
[0092]
[0093] In the formula: E is the water retention rate of the dust sample, %; M0 is the mass of the dry dust sample, g; M1 is the mass of the dust sample after spraying the road composite dust suppressant, g; M2 is the mass of the dust sample measured after evaporation for n hours, g.
[0094] The calculation formula of dust suppression rate is as follows:
[0095]
[0096] Where: S is the dust suppression rate (%); C0 is the average dust concentration in the untreated area (μg / m 3 ), C1 is the average dust concentration in the area where the road composite dust suppressant is sprayed (μg / m 3 ).
[0097] The performance test results of water retention rate and dust suppression rate after spraying the road composite dust suppressant for 3 hours are shown in Table 1.
[0098] Table 1
[0099] Viscosity value Water retention rate Dust suppression rate Example 1 23.3cp 92.56% 92.64% Example 2 22.4cp 92.97% 93.01% Example 3 21.2cp 93.12% 92.58% Example 4 22.4cp 92.57% 94.37% Example 5 23.8cp 93.24% 94.94% Comparative Example 1 21.6cp 79.85% 73.45% Comparative Example 2 22.9cp 76.38% 74.58% Comparative Example 3 20.2cp 74.56% 71.27%
[0100] It can be seen from the test results in Table 1 that the composite dust suppressant provided by the present invention has a dust suppression rate and a water retention rate of more than 90% for open-pit limestone mine roads, and has good dust suppression performance.
[0101] The composite dust suppressant for open-air limestone mine roads disclosed by the present invention has excellent dust suppression effect and can effectively capture fine dust in the air. Moreover, the present invention is non-corrosive to metals, meets industrial environmental protection requirements, can be used for normal industrial production, is safe and environmentally friendly, and is very suitable for promotion and use to reduce dust pollution.
[0102] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A composite road dust suppressant, characterized in that: The raw material components include the following parts by weight: 1.2-3.8 parts of modified xanthan gum, 0.6-0.8 parts of flue-cured tobacco extract and 0.4-0.5 parts of zirconium oxide; The modified xanthan gum is prepared by grafting and copolymerizing acrylamide monomer with xanthan gum.
2. The composite road dust suppressant according to claim 1, characterized in that: The reaction temperature of the graft copolymerization is 50-90° C., and the reaction time is 4 hours.
3. The composite road dust suppressant according to claim 1, characterized in that: When the graft copolymerization reaction is carried out, a crosslinking agent and an initiator are also added into the reaction system; the mass ratio of the xanthan gum, acrylamide monomer, crosslinking agent and initiator is: 1:(13-17):(0.3-0.9):(0.1-0.5).
4. The composite road dust suppressant according to claim 1, characterized in that: The preparation method of the flue-cured tobacco extract comprises the following steps: The flue-cured tobacco is boiled with water, and the filtrate is concentrated and adjusted to have an alcohol content of 28-38%. The precipitate is discarded after centrifugation, and the alcohol content of the filtrate is adjusted again to have an alcohol content of 55-60%. The precipitate is collected after standing and dried to obtain the flue-cured tobacco extract.
5. A composite road dust suppressant emulsion, characterized in that: Contains the raw material components described in claim 1.
6. The composite road dust suppressant emulsion according to claim 5, characterized in that: The raw material components include the following parts by weight: 1.2-3.8 parts of modified xanthan gum, 0.6-0.8 parts of flue-cured tobacco extract, 0.4-0.5 parts of zirconium oxide, 0.4-0.8 parts of surfactant, 5-8 parts of glycerol and 80-90 parts of water.
7. The composite road dust suppressant emulsion according to claim 5, characterized in that: The surfactant is one or more of Taiko oil, cocamidopropyl betaine or sodium dodecylbenzene sulfonate.
8. The method for preparing the composite road dust suppressant emulsion according to claim 6, characterized in that: The following steps are involved: The modified xanthan gum, flue-cured tobacco extract and zirconium oxide are mixed, water is added to the obtained mixture, and the mixture is stirred for reaction, and then a surfactant and glycerin are added to the reaction system to obtain the composite road dust suppressant.
9. Use of the composite road dust suppressant according to claim 1 or the composite road dust suppressant emulsion according to claim 5 in dust suppression on open-pit limestone mine roads.
